Drilling Pipe Corrosion Reduction Using Natural, Biodegradable, and Environmentally Friendly Additive to the Drilling Fluid - Jaf, Pshtiwan T.; Ali, Jafar A.; Razzaq, Ayad A. A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Corrosion is one of the disasters attacking the drilling tools, particularly the drill pipes. Drilling fluid is the corrosive that increase the rate of corrosion in the pipes. In this study, it is intended to reduce the corrosivity of drilling fluid using a Prosopis farcta powder material. A natural, biodegradable, and environmentally friendly additive is added to the fluid in different particle sizes and amounts to obtain the lowest corrosion rate. Experiments are conducted in a well-like environment (high pressure high temperature filter press) over a wide range of parameters including pressure, temperature, and properties of the drilling fluid under dynamic conditions. The aim is to eliminate or reduce the corrosivity of the mud as well as to control the losses. The results showed a lower corrosion rate, 0.0029 mm/year, using P. farcta material in comparison with those obtained by researchers in the previous studies.